Studying the influence of guava fruitghurt on Escherichia coli coloniesin rats’ digestive tracts - K. P. Dewi, Ania; D Mahendra, Gilang; Ambarukmi, Fransiska (ACTA Medical Health Sciences, 2023)
A balanced microbiota can play a role in the host's defense mechanism against pathogenic infections. E. coli is a harmless and beneficial commensal. An increase in bacteria will change their nature to become pathogens that can cause gastrointestinal disease, such as diarrhea. The management of such condition can be managed in several ways, including the consumption of probiotics. Fruitghurt is a variant of yogurt that is made using fruit juice. L. acidophilus is resistant to stomach acid; it can inhibit the growth of pathogenic bacteria and can maintain the number of live bacteria up to 107/ml. The research design used was experimental. The research subjects were white rats (Rattus norvegicus), with the Wistar strain as many as 27 rats. They were divided into 3 groups: 1. K (-),a negative control group that was not induced by E. coli and was not given fruitghurt; 2. K (+)a positive control group that was given E.coli, but not treated by fruitghurt; and 3. P1, the treatment group that was induced with E.coli and treated by fruitghurt. The results showed that guava fruitghurt could reduce E. coli colonies. The number of E. coli colonies after being given fruitghurt was 161, while in the rats that were not given fruitghurt, there were 258 colonies. Guava fruitghurt can reduce E. coli because of the flavonoid, tannin, and polyphenol contents found in red guava, which act as protein coagulators, antibacterials, and toxins, as well as L. acidophilus bacteria that can inhibit the growth and attachment of pathogenic bacteria in the digestive tract and inhibit the spread of pathogenic bacteria. DOI : 10.35990/amhs.v2n2.p73-80 REFERENCE Bagcchi S. WHO's Global Tuberculosis Report 2022. Lancet Microbe. 2023;4(1):e20. Pandey D, Yadav A. Efficacy of gene xpert over other diagnostic modalities of tuberculosis among children. Int J Contemp Pediatr. 2019;6(4):1545-51. Shi J, Dong W, Ma Y, Liang Q, Shang Y, Wang F, et al. GeneXpert MTB/RIF Outperforms Mycobacterial Culture in Detecting Mycobacterium tuberculosis from Salivary Sputum. Biomed Res Int. 2018;2018:1514381. Mechal Y, Benaissa E, El Mrimar N, Benlahlou Y, Bssaibis F, Zegmout A, et al. Evaluation of GeneXpert MTB/RIF system performances in the diagnosis of extrapulmonary tuberculosis. BMC Infect Dis. 2019;19(1):1069. Mukhida S, Vyawahare CR, Mirza SB, Gandham NR, Khan S, Kannuri S, et al. Role of GeneXpert MTB/RIF assay for the diagnosis of cervical lymph node tuberculosis and rifampicin resistance. Tzu Chi Med J. 2022;34(4):418-22. Vassall A, Siapka M, Foster N, Cunnama L, Ramma L, Fielding K, et al. Cost-effectiveness of Xpert MTB/RIF for tuberculosis diagnosis in South Africa: a real-world cost analysis and economic evaluation. Lancet Glob Health. 2017;5(7):e710-e9. Khumsri J, Hanvoravongchai P, Hiransuthikul N, Chuchottaworn C. Cost-Effectiveness Analysis of Xpert MTB/RIF for Multi-Outcomes of Patients With Presumptive Pulmonary Tuberculosis in Thailand. Value Health Reg Issues. 2020;21:264-71. World Health Organization. Automated Real-Time Nucleic Acid Amplification Technology for Rapid and Simultaneous Detection of Tuberculosis and Rifampicin Resistance: Xpert MTB/RIF Assay for the Diagnosis of Pulmonary and Extrapulmonary TB in Adults and Children: Policy Update. Geneva: WHO; 2013. Chakraborty A, Ramaswamy S, Shivananjiah AJ, Puttaswamy RB, Chikkavenkatappa N. The role of genexpert in the diagnosis of tubercular pleural effusion in India. Adv Respir Med. 2019;87(5):276-80. Directorate General of Prevention and Disease Control. Tuberculosis Control in Indonesia 2022. Jakarta: Ministry of Health Republic of Indonesia; 2022. Gurung SC, Dixit K, Rai B, Dhital R, Paudel PR, Acharya S, et al. Comparative Yield of Tuberculosis during Active Case Finding Using GeneXpert or Smear Microscopy for Diagnostic Testing in Nepal: A Cross-Sectional Study. Trop Med Infect Dis. 2021;6(2). Agrawal M, Bajaj A, Bhatia V, Dutt S. Comparative Study of GeneXpert with ZN Stain and Culture in Samples of Suspected Pulmonary Tuberculosis. J Clin Diagn Res. 2016;10(5):DC09-12. Agizew T, Boyd R, Auld AF, Payton L, Pals SL, Lekone P, et al. Treatment outcomes, diagnostic and therapeutic impact: Xpert vs. smear. A systematic review and meta-analysis. Int J Tuberc Lung Dis. 2019;23(1):82-92. Orlando S, Triulzi I, Ciccacci F, Palla I, Palombi L, Marazzi MC, et al. Delayed diagnosis and treatment of tuberculosis in HIV+ patients in Mozambique: A cost-effectiveness analysis of screening protocols based on four symptom screening, smear microscopy, urine LAM test and Xpert MTB/RIF. PLoS One. 2018;13(7):e0200523. Subuh M, Priohutomo S, Widaningrum C. Pedoman Nasional Pengendalian Tuberkulosis. In: Dinihari TN, Siagian V, editors. Jakarta: Direktorat Jenderal Pengendalian Penyakit dan Penyehatan Lingkungan Kementerian Kesehatan Republik Indonesia; 2014. Baik Y, Rickman HM, Hanrahan CF, Mmolawa L, Kitonsa PJ, Sewelana T, et al. A clinical score for identifying active tuberculosis while awaiting microbiological results: Development and validation of a multivariable prediction model in sub-Saharan Africa. PLoS Med. 2020;17(11):e1003420. Hanifa Y, Fielding KL, Chihota VN, Adonis L, Charalambous S, Foster N, et al. A clinical scoring system to prioritise investigation for tuberculosis among adults attending HIV clinics in South Africa. PLoS One. 2017;12(8):e0181519. Balcha TT, Skogmar S, Sturegard E, Schon T, Winqvist N, Reepalu A, et al. A Clinical Scoring Algorithm for Determination of the Risk of Tuberculosis in HIV-Infected Adults: A Cohort Study Performed at Ethiopian Health Centers. Open Forum Infect Dis. 2014;1(3):ofu095. Zimba O, Tamuhla T, Basotli J, Letsibogo G, Pals S, Mathebula U, et al. The effect of sputum quality and volume on the yield of bacteriologically-confirmed TB by Xpert MTB/RIF and smear. Pan Afr Med J. 2019;33:110. Gordis L. Epidemiology. 5th ed. Philadelphia: Elsevier Saunders; 2014. Nahm FS. Receiver operating characteristic curve: overview and practical use for clinicians. Korean J Anesthesiol. 2022;75(1):25-36.